Complete Genome Sequence of Yersinia enterocolitica subsp. palearctica Serogroup O:3 - Batzilla, Julia (American Society for Microbiology, 2011)
We report here the first finished and annotated genome sequence of a representative of the most epidemiologically successful Yersinia group, Y. enterocolitica subsp. palearctica strain Y11, serotype O:3, biotype 4. This strain is a certified type strain of the German DSMZ collection (DSM no. 13030; Yersinia enterocolitica subsp. palearctica) that was isolated from the stool of a human patient (H. Neubauer, S. Aleksic, A. Hensel, E. J. Finke, and H. Meyer. Int. J. Med. Microbiol. 290:61–64, 2000).